Length-weight relationship and condition factor of spotted barb Barbodes binotatus (Valenciennes, 1842) in Barambai River Samarinda East Kalimantan - Jusmaldi Jusmaldi; Nova Hariani (Jurnal Iktiologi Indonesia, 2018)
Biology of the spotted barb Barbodes binotatus (Valenciennes, 1842) in Barambai River, east Kalimantan is unknown. This study aimed to analyses sizes of fish, sex ratio, length-weight relationship and condition factor of the spotted barb. A total of 347 fish samples were collected by several gears in Barambai River from August to October 2017. The results of this research showed that the total length of the fish ranged from 45.67 to 146.01 mm and weight ranged from 1.27-43.34 g. The sex ratio of male and female were 1:1.12. The length-weight equations for males was W = 1x10-5 L3.063, W = 8x10-6L3.108 for females, and W = 9 x 10-6 L3.091 for both sexes. The condition factor (K) for the spotted barb was ranged between 0.826 – 2.214 with mean value of 1.163. Abstrak Biologi ikan wader bintik dua Barbodes binotatus (Valenciennes, 1842) di Sungai Barambai, Kalimantan Timur belum diketahui. Penelitian ini bertujuan menganalisis ukuran ikan, nisbah kelamin, hubungan panjang bobot, dan faktor kon-disi. Total 347 sampel ikan dikumpulkan dengan menggunakan berbagai alat tangkap di Sungai Barambai dari bulan Agustus sampai Oktober 2017. Hasil penelitian menunjukkan bahwa panjang total ikan berkisar dari 45,67 sampai 146,01 mm dan bobot tubuh berkisar 1,27- 43,34 gram. Nisbah kelamin jantan dan betina 1: 1,12. Model hubungan panjang bobot ikan jantan W = 1x10-5 L3,063, ikan betina W = 8x10-6L3,108,dan keseluruhan jenis ikan W = 9 x 10-6 L3,091. Faktor kondisi (K) ikanwader bintik dua berkisar antara 0,826 - 2,214 dan rata-rata 1,163.